Ferroptosis and bone metabolic diseases: the dual regulatory role of the Nrf2/HO-1 signaling axis - Nan, Wei; Zhou, Wen-Ming; Zi, Jian-Lan; Shi, Yong-Qiang; Dong, Yan-Bo; Song, Wei; Ma, Yan-Chao; Zhang, Hai-Hong (Frontiers in Cell and Developmental Biology, 2025)
Ferroptosis, an iron-dependent form of regulated cell death characterized by lipid peroxidation, has emerged as a pivotal mechanism in bone disorders including osteoporosis and osteonecrosis. The nuclear factor erythroid 2–related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling axis plays a paradoxical role—contributing to cytoprotection under oxidative stress, yet potentially promoting ferroptosis through excessive iron accumulation. This review summarizes how the Nrf2/HO-1 pathway modulates ferroptosis across osteoblasts, osteoclasts, and osteocytes, and its impact on bone homeostasis. We explore the pathway’s involvement in the shift from physiological bone remodeling to pathological bone loss. Given its dual role, the Nrf2/HO-1 axis represents both a challenge and an opportunity for therapeutic intervention. Understanding its context-specific functions is essential for developing precise, ferroptosis-targeted strategies in bone disease treatment.